A korszerű reklámozás világa - Pajor Barbara (2016)
In my thesis I intended to summarize my knowledge of theoretical and practical effects of the commercials. In the first part of my thesis I considered being important to present the advertisement as a special type of mass media, and to demonstrate my personal opinion , highlighted by grouping the sensory effects of advertising tools. The advertising design process using more literature I prestented and tried to delineate the basic elements, features, advantages and disadvantages of the various advertising media. The advertising mechanism of action was analysed by ADA model. I studied the psychological impact of advertising on the basis of examination of the literature and my opinion. I highlighted the purpose and means of manipulation for consumers. I consider myself fortunate, because I had the opportunity to spend my 14- week -practice at Szombathely Television and I could come to know the world of television. In my thesis I examined the television commercials over posters. I presented three commercials explaned in what way affect us viewers the celebrity ads. I could know modern advertising tools via Internet and social networks all the way to a new generation of equipment. I knew previous researches studied the world of onlie shopping and the Internet use. Also I paid attention to the current analyzes, surveys and the tv watching on the Internet. In the second half of my thesis I analysed the results of my survey on the basis of my research hypothesis. I was looking for answers to what media tools used in advertising, the level of satisfaction, how aroused pulses of different advertisements, ads actually what they think about these. Survey results were suprising to me when the first hypothesis was confirmed, according to which the older age group also takes a modern, streamlined communication tools instead of the traditional, outdated media. The results of my research contradict the second hypothesis. That does not correspond to reality that the often repeated advertisements produce negative impression. However, the third assumption is that more people use the werb on requests, such an entertaintment, it has been proved on the basis of my questionnnaire survey.